2011
DOI: 10.1002/jso.22035
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of the plasminogen activator inhibitor‐1 is associated with an increased risk of endometrial cancer

Abstract: Individuals with PAI-1 rs1799889 4G/4G genotype were at significantly higher risk of endometrial cancer in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…However, no significant difference in allele frequency was evident between the two. Other criteria for dividing the subjects into various groups were determined according to previous reports as well as clinical significance [4], [5]. The results showed that the SNP C variant carriers had higher pathological grade and deeper myometrial invasion (OR = 2.042 and OR = 2.233 respectively) compared to G carriers.…”
Section: Resultsmentioning
confidence: 99%
“…However, no significant difference in allele frequency was evident between the two. Other criteria for dividing the subjects into various groups were determined according to previous reports as well as clinical significance [4], [5]. The results showed that the SNP C variant carriers had higher pathological grade and deeper myometrial invasion (OR = 2.042 and OR = 2.233 respectively) compared to G carriers.…”
Section: Resultsmentioning
confidence: 99%
“…We defined studies that scored ≥7 as having high methodological quality, and we judged 4 (21,22,26,35) of the 21 studies to be of low quality (score of 6) primarily due to the absence of a definition of controls and a lack of a description of comparability between cases and controls.…”
Section: Resultsmentioning
confidence: 99%
“…To date, a number of molecular epidemiological studies have been performed to evaluate the association between PAI-1 promoter 4G/5G polymorphism and risks for different types of tumor, including breast cancer (12–17), colorectal cancer (3,1820), ovarian cancer (21,22), oral cancer (23,24), endometrial cancer (25,26) and other cancers (27,28), in diverse populations However, the observed associations of these studies were inconsistent and a single study may be insufficient to detect a possible small effect of the polymorphism on cancer, particularly when the sample size is relatively small. Hence, we performed a meta-analysis of all eligible studies to derive a more precise estimation of the association of PAI-1 promoter 4G/5G polymorphism with cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…And results of study of Vossen et al did not support an effect of PAI 1 4G/5G on colorectal cancer risk [59]. Palmirotta et al [62,63]. For colorectal cancer Försti et al in their work demonstrates that the 4G/4G genotype is associated with shorter survival because it is linked more to Dukes C tumors, in contrast to the 5G/5G genotype, which is associated more with tumors stage A and B [34].…”
Section: Discussionmentioning
confidence: 96%
“…The presence of 4G/4G genotype in the promoter of the PAI 1 gene increases the risk of thrombosis. This polymorphism is also often associated with other diseases such as heart attack [24] or diabetes mellitus [25], and with other types of cancers such as endometrial cancer or breast cancer [26,27]. The distribution of each variant is different in different populations, the 4G/4G genotype is more common among Asians (59%) [28] and Caucasian populations (51%) [29], Spaniards (47%) [30] and Indians (54%) [31], than for Mexicans (34%) [32] and African-Americans (24%) [33].…”
mentioning
confidence: 99%